Immunocytochemical localization of beta II subspecies of protein kinase C in rat brain. - Saito, N (1989)
The distribution of a subspecies of protein kinase C (PKC) encoded by the beta II sequence in rat central nervous tissue was demonstrated immunocytochemically by using antibodies raised against an oligopeptide having a partial sequence specific for the beta II PKC. The beta II PKC immunoreactivity was widely but discretely distributed in the brain. The distribution of the beta II PKC immunoreactivity differed from that of the beta I and gamma PKC subspecies. The beta II PKC immunoreactivity was found in the perikarya, dendrites, and axons of neuronal cells. Few if any glial cells were stained. Immunoreactive neurons were present in the anterior olfactory nucleus, olfactory tubercle, amygdaloid complex, caudate-putamen, accumbens nucleus, claustrum, dorsal part of the lateral septal nucleus, CA1 region of the hippocampus, subiculum, medial habenular nucleus, cerebral cortex, nucleus of the spinal tract of the trigeminal nerve, nucleus of the solitary tract, and substantia gelatinosa of the spinal cord. In these neurons, the beta II PKC immunoreactivity was seen mainly in the form of cytoplasmic dots and, in some cases, diffusely in the cytoplasm. Under electron microscopy, these immunoreactive large dots appeared to be associated with the Golgi complex, suggesting that the beta II PKC plays a specialized function at the Golgi complex in certain neuronal cell types.